Renal clearance and daily excretion of cortisol and adrenal androgens in patients with rheumatoid arthritis and systemic lupus erythematosus. Issue 8 (12th July 2004) - Straub, R H; Weidler, C; Demmel, B; Herrmann, M; Kees, F; Schmidt, M; Schölmerich, J; Schedel, J
Abstract : Background: In rheumatoid arthritis (RA) and systemic lupus erythematosus (SLE), patients demonstrate low levels of adrenal hormones. Objective: To investigate whether increased renal clearance and daily excretion contribute to this phenomenon. Methods: Thirty patients with RA, 32 with SLE, and 54 healthy subjects (HS) participated. Serum and urinary levels of cortisol, cortisone, 17-hydroxyprogesterone (17OHP), androstenedione, dehydroepiandrosterone (DHEA), and DHEA sulphate (DHEAS) were measured. Results: Clearance of DHEAS and DHEA was lower in patients than in HS, and clearance of androstenedione was somewhat higher in patients than in HS, but daily excretion of this latter hormone was low. Clearance of cortisol, cortisone, and 17OHP was similar between the groups. The total molar amount per hour of excreted DHEA, DHEAS, and androstenedione was lower in patients than HS (but similar for cortisol). Serum DHEAS levels correlated with urinary DHEAS levels in HS and patients, whereby HS excreted 5–10 times more of this hormone than excreted by patients. Low serum levels of adrenal androgens and cortisol in patients as compared with HS were confirmed, and proteinuria was not associated with changes of measured renal parameters. Conclusions: This study in patients with RA and SLE demonstrates that low serum levels of adrenal androgens and cortisol are not due to increased renal clearance and daily loss of these hormones. Decreased adrenal production or increased conversion or conjugation to downstream hormones are the most likely causes of inadequately low serum levels of adrenal hormones in RA and SLE.